2020
DOI: 10.1111/iwj.13507
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy in spinal fusion patients

Abstract: Post-operative wound complications are some of the most common acute complications following spine surgery. These surgical site infections (SSI) contribute to increased healthcare related costs. Negative pressure wound therapy (NPWT) has long been used for treatment of soft tissue injury or defects. NPWT may reduce the incident of SSI following spinal fusion procedures; however, its potential applications need further clarification. Thus, we conducted a retrospective analysis of two cohorts to compare NPWT to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…The 84 studies identified encompassed cardiac surgery (n = 8), general abdominal surgery (n = 21), obstetric and gynecologic surgery (n = 8), orthopedic surgery (n = 16), plastic surgery (n = 16), and vascular surgery (n = 15). 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 84 studies identified encompassed cardiac surgery (n = 8), general abdominal surgery (n = 21), obstetric and gynecologic surgery (n = 8), orthopedic surgery (n = 16), plastic surgery (n = 16), and vascular surgery (n = 15). 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
“…Dressings used in the SOC population varied and included gauze dressings, antimicrobial hydrofiber dressings, absorbent dressings, hydrocolloid dressings, occlusive dressings, or foam dressings. 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this finding was not statistically significant, likely owing to the small sample size [ 57 ]. A 2021 retrospective matched cohort study demonstrated that Prevena NPWT is associated with reduced incidence of SSI when controlling for sex and BMI in patients undergoing posterior spinal fusions [ 58 ]. However, the control cohort in this study had an unusually high incidence of SSI (7.1% or 3 out of 42 patients) [ 58 ].…”
Section: Npwt In Spinementioning
confidence: 99%
“…A 2021 retrospective matched cohort study demonstrated that Prevena NPWT is associated with reduced incidence of SSI when controlling for sex and BMI in patients undergoing posterior spinal fusions [ 58 ]. However, the control cohort in this study had an unusually high incidence of SSI (7.1% or 3 out of 42 patients) [ 58 ]. A 2021 retrospective, non-randomized study of a small patient population showed that the use of NPWT in patients with metastatic spine disease and instability or accelerated neurological decline resulted in reduced incidence of SSI postoperatively, which is important given the high risk of wound complications in this population [ 59 ].…”
Section: Npwt In Spinementioning
confidence: 99%